2012
DOI: 10.1007/s00408-012-9418-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Second Lung Cancer in Hodgkin’s Lymphoma Survivors: A Meta-analysis

Abstract: The current meta-analysis provided a detailed estimate of the risk of SLC among HL survivors. The obtained results may provide guidelines concerning lung cancer screening for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 56 publications
0
25
0
1
Order By: Relevance
“…Prior NSCLC is a known risk factor for developing second primary NSCLC at estimated rates of 1-2% per year with increasing tobacco exposure conferring higher risk 6, 7 . Population-based and institutional studies have demonstrated that survivors of head and neck cancer as well as Hodgkin's lymphoma are also at increased risk of developing new primary lung cancer 8, 9 . However, it is unclear whether the antecedent cancer directly increases risk or whether confounding factors play a role.…”
Section: Introductionmentioning
confidence: 99%
“…Prior NSCLC is a known risk factor for developing second primary NSCLC at estimated rates of 1-2% per year with increasing tobacco exposure conferring higher risk 6, 7 . Population-based and institutional studies have demonstrated that survivors of head and neck cancer as well as Hodgkin's lymphoma are also at increased risk of developing new primary lung cancer 8, 9 . However, it is unclear whether the antecedent cancer directly increases risk or whether confounding factors play a role.…”
Section: Introductionmentioning
confidence: 99%
“…Risks of second primary colorectal cancers are doubled [10] but might only be increased in tumours of the proximal colon [11]. A five-fold increase in risk of primary lung cancers following Hodgkin’s lymphoma has been reported [12] and risks of second primary head & neck cancers are raised [13]. …”
Section: Introductionmentioning
confidence: 99%
“…Retrospective data suggest that larger radiation fields are associated with an increased risk of second malignancies and a higher integral radiation dose is associated with an increased risk of death from a second malignancy [7][8][9]. The incidence of breast and lung cancers, among others, has been documented to be elevated in cHL patients after treatment, resulting in poor outcomes [10][11][12][13][14][15][16][17]. However, a recently published SEER analysis of early-stage cHL has demonstrated that the use of RT in these patients improves overall survival (OS) without increasing the rate of second malignancies [18].…”
Section: Introductionmentioning
confidence: 99%